2016
DOI: 10.1371/journal.pone.0151835
|View full text |Cite
|
Sign up to set email alerts
|

Status and Power Do Not Modulate Automatic Imitation of Intransitive Hand Movements

Abstract: The tendency to mimic the behaviour of others is affected by a variety of social factors, and it has been argued that such “mirroring” is often unconsciously deployed as a means of increasing affiliation during interpersonal interactions. However, the relationship between automatic motor imitation and status/power is currently unclear. This paper reports five experiments that investigated whether social status (Experiments 1, 2, and 3) or power (Experiments 4 and 5) had a moderating effect on automatic imitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…Likewise, some researchers did not find reduced automatic imitation in individuals with autism [ 62 64 ]. Finally, Farmer et al [ 108 ] did not find an influence of social status and power on automatic imitation. Thus, in light of these contradictory findings, more research is needed in order to draw specific conclusions about the degree to which social factors facilitate automatic imitation.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, some researchers did not find reduced automatic imitation in individuals with autism [ 62 64 ]. Finally, Farmer et al [ 108 ] did not find an influence of social status and power on automatic imitation. Thus, in light of these contradictory findings, more research is needed in order to draw specific conclusions about the degree to which social factors facilitate automatic imitation.…”
Section: Discussionmentioning
confidence: 96%
“…While differential levels of power within a dyad can modulate spontaneous facial mimicry to emotional expressions, does this influence extend to more rudimentary (simpler, less emotional) forms of mimicry? This question was addressed by a series of studies that manipulated social status or power levels in the participant and tested its effect on a basic task that assesses automatic imitation of observed finger movements (Farmer et al 2016). Results revealed that status and power manipulations did not impact spontaneous finger mimicry in this task.…”
Section: Power In Contextmentioning
confidence: 99%
“…Before reviewing the literature further, it is worth noting that there are several forms of imitative behaviour. Farmer, Carr, Svartdal, Winkielman, and de C Hamilton (2016) identify three common forms of imitation in the literature. The first of these is behavioural mimicry, the tendency of people to naturally copy others' movements during social interactions, which is usually studied via naturalistic observation paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that the strength of interpersonal relationship between actor and imitator ( Maister & Tsakiris, 2016 ) and group identity ( Gleibs, Wilson, Reddy, & Catmur, 2016 ; Rauchbauer, Majdandžić, Hummer, Windischberger, & Lamm, 2015 ; Rauchbauer, Majdandžić, Stieger, & Lamm, 2016 ) can also modulate AI. However, it should be noted that other socially relevant factors such as social status and power do not appear to modulate AI ( Farmer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%